Retour sur Manuel Núñez de Arenas (1886-1951). Notes pour une biographie - Jean-Louis Guereña (Cahiers de Civilisation Espagnole Contemporaine)
We propose to recall, first, the decisive contribution of French Hispanicism and of Manuel Tuñón de Lara in particular to the knowledge of the biography of Manuel Núñez de Arenas and his work, emphasizing his role in the creation of the « New School ». We then briefly indicate some of the documentary sources which we have at our disposal on our character, his archives, his library and his correspondence, as well as some indications on his own publications, in particular his numerous collaborations in the periodical press. We will conclude these pages by emphasizing the main characteristics of his personality as an intellectual engaged in a constant struggle for popular education and culture.